Effect of N, P and K fertilisers and their interactions in a long-term experiment on winter barley (Hordeum vulgare L.) - Surányi, Szilvia; Izsáki, Zoltán (Acta Agraria Debreceniensis, 2016)
The aim of this work was to analyse the effect of K, P and N supplies on the yield of winter barley in a long-term mineral fertilisation experiment with clearly distinct soil nutrient supply levels in order to develop fertilisation guidelines for winter barley growers. The experiment was set up in 1989 on a chernozem meadow soil calcareous in the deeper layers, applying all possible combinations of 4 levels each of N, P and K fertiliser, giving a total of 64 treatments.The results of analyses performed in 2011 and 2012 can be summarised as follows:• In 2011, when rainfall supplies were deficient in the shooting phase, improved K supplies (324 mg kg-1 AL-K2O) increased the grain yield, but in 2012, when rainfall supplies were more evenly distributed, K supply levels in the range 210–335 mg kg-1 AL-K2O had no significant influence on the yield of winter barley.• An analysis of the P treatments revealed that, compared to the 119–133 mg kg-1 AL-P2O5 level (P0), better P supplies (186–251 mg kg-1) led to a significant increase in the grain yield.• In both years rising N rates significantly increased the yield up to an annual N rate of 160 kg ha-1.      4. A K×N interaction could only be detected in the nutrient supplies of winter barley in 2011. The yield-increasing effect of N fertiliser was more    pronounced at better K supply levels, while K fertiliser led to higher yields in the case of better N supplies.